Bacteriological and Physicochemical Quality of Bottled Water Brands in Ota, Ogun State, Nigeria: Public Health Implications - Seriki, Abiodun; Essien, Enobong; Umanu, Goddey; Obi, Chioma; Olumuyiwa, Emmanuel; Asomugha, Ugonnaya; Adeniji, Folakemi (FUDMA Journal of Sciences, 2026)
Water is essential for human survival and must be managed carefully to prevent health risks associated with industrial or bacterial contamination. Hence, this study provided a baseline assessment of the quality and microbiological safety of the most widely consumed bottled drinking water brands in Ota, Ogun State, Nigeria.Nine individual bottled water samples representing nine entirely distinct brands were analysed. Each distinct brand was processed in duplicate for viable bacterial population, pH and chloride content. Gram staining, biochemical tests, and the Analytical Profile Index (API) were used to identify the bacteria. The pH and the chloride content of the samples ranged from 5.19 to 6.96 and 6.92 to 28.58 mg/L, respectively. Six of the nine water samples were below the recommended pH range (6.5 to 8.5) for drinking water. Although a notable negative trend was observed between pH and TVC (rs = -.567, p = .112) and a minor positive trend between chloride and TVC (rs = .133, p = .732), neither relationship was statistically significant at the 0.05 level. However, causality cannot be inferred from this dataset due to the small sample size.In addition, growth of 7 isolates was observed: Aeromonas hydrophila, Klebsiella pneumoniae, Providencia rettgeri, Chromobacterium violaceum, Enterobacter intermedius, Enterobacter cloacae, and Escherichia coli. Even though bottled water was supposed to be devoid of microorganisms, various bacteria were discovered in it, according to these findings. Water distribution systems must be adequately maintained, and awareness of the potential risks of consuming unsanitary water should be improved.
Keywords: Chlorides, Drinking water, Linear models, Nigeria, pH